1983
DOI: 10.1002/j.1939-4640.1983.tb00748.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Study on the Initiation of Acid Phosphatase Secretion in the Human Prostate Cytochemistry and Biochemistry of Acid Phosphatases IV

Abstract: Acid phosphatase was purified from human prostatic tissue and from seminal plasma. Antisera to antigens from both sources were raised in rabbits. These antisera have been used for immunohistochemical localization of the respective antigens in the prostates of neonatal, infantile, prepubertal, and adult individuals. Immunoreactivity of the prostatic epithelium with the seminal fluid-derived antigen developed progressively in pubertal specimens with increasing age. It was not present in fetal and infantile organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…Similar findings have been reported by other authors (Abrahamsson 1988). The present finding of labeling of the vacuoles with the lamp antibody is clearly in favor of the previously suggested relationship between prostatic secretory vacuoles and lysosomes (Aumüller 1979).…”
Section: Immunoelectron Microscopy Of Lamp 2 In the Human Prostatesupporting
confidence: 69%
See 2 more Smart Citations
“…Similar findings have been reported by other authors (Abrahamsson 1988). The present finding of labeling of the vacuoles with the lamp antibody is clearly in favor of the previously suggested relationship between prostatic secretory vacuoles and lysosomes (Aumüller 1979).…”
Section: Immunoelectron Microscopy Of Lamp 2 In the Human Prostatesupporting
confidence: 69%
“…After clotting, the antiserum was obtained by centrifugation and was purified by absorption with human seminal secretory proteins adsorbed to nitrocellulose paper strips. A polyclonal rabbit antibody, directed against the secretory prostatic acid phosphatase isoenzyme was obtained from Prof. Seitz from our department (Aumüller et al 1983;Seitz and Aumüller 1985). Secondary antimouse or anti-rabbit IgG antibodies, either FITC or CY3-labeled, unlabeled anti-rabbit IgG and soluble peroxidase-anti-peroxidase complex (PAP) were purchased from Dianova (Hamburg, Germany).…”
Section: Antiseramentioning
confidence: 99%
See 1 more Smart Citation
“…The respective isoenzymes, which are either secretory (antigen I) or lysosomal (antigen II), have been purified and used for antibody production. As has been shown earlier [2], both antibodies have a markedly different binding pattern in the maturing prostate. It was demonstrated that immunoreactivity against secretory acid phosphatase (isoenzyme 2a) develops progressively within prostatic secretory cells during puberty, while the lysosomal isoenzyme (isoenzyme 3) is already present in the fetal and prepubertal gland.…”
Section: Introductionsupporting
confidence: 72%
“…Intermediate forms between basal and luminal cells were not observed in the developing human prostate [14]. By 14 years of age, secretory PAP and PSA immunoreactivity are detected in prostatic epithelium and PAS-positive cells gradually become less and are absent in the normal adult prostate [4,17].…”
Section: Human Prostate Developmentmentioning
confidence: 94%